HISTORY OF PILGRIMAGE TOURISM AND ITS ROLE AND IMPORTANCE IN THE TOURISM SECTOR (International journal of artificial intelligence, 2026)
Pilgrimage tourism includes travel by representatives of various religions to sacred places. This article analyzes the history of pilgrimage tourism, its role in the tourism sector, and its economic and cultural significance. It also emphasizes the importance of developing pilgrimage tourism in Uzbekistan, improving infrastructure, creating favorable conditions for foreign and domestic tourists, and introducing digital technologies. The development of pilgrimage tourism not only brings economic benefits but also serves to strengthen cultural exchange and national identity.